Awareness and compliance to information ethics by undergraduate students in University of Ibadan, Nigeria (2020)
Information is widely available these days, not only in libraries but also on the internet. From preliminary investigation, most students in higher institutions use Information without proper paraphrasing and acknowledgement to authors. This is a complex issue that could result in plagiarism which needs to be fixed. The study therefore examined awareness and compliance to Information ethics by undergraduate students in University of Ibadan, Nigeria. The population for the study comprised 12,178 undergraduates from the thirteen Faculties in University of Ibadan as at 2016/2017 academic Session. Data was collected from 214 undergraduates selected with the use of two-stage sampling technique in the University of Ibadan. Structured questionnaire with reliability co-efficient of r=0.78 was used to elicit responses from the respondents. Frequency counts, percentage, mean and Standard deviation was used to provide answer to the three research questions raised for the study. Findings revealed a moderate level of compliance with Information ethics, most of the respondents indicated that they always try to avoid plagiarism while using intellectual property; most of the respondents occasionally observe every bit of the ethical Standards that guides the use of intellectual property and further the main reasons for non-compliance with Information ethics. The study recommends that more enlightenment of the undergraduate students on ethical Standards of intellectual property utilisation should be put in place in order to totally eradicate plagiarism and enhance knowledge infrastructure development in Nigeria.